1999
DOI: 10.1093/humrep/14.2.566
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in CA 125 and CA 15 3 serum concentrations during spontaneous ovulatory cycles

Abstract: The aim of this study was to investigate cycle dependent changes of serum CA 125 and CA 15-3 concentrations during spontaneous ovulatory cycles. Twenty apparently healthy women with spontaneous menstrual cycles attending our infertility clinic were included. Of these women, 18 had occluded tubes as a result of sterilization. Ovulation was confirmed by luteinizing hormone test and ultrasonography and, to exclude endometriosis, a laparoscopy was performed. Serum samples for CA 125, CA 15-3, 17 beta-oestradiol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 24 publications
4
42
0
2
Order By: Relevance
“…18,19 The CA125 released by the endometrium may reach the blood stream and lymphatic circulation via the peritoneal route, starting from retrograde menstruation, thereby allowing contact with local inflammatory reactions and thus releasing coelomic CA125. 20 Another explanation for the increased levels of CA125 in the bloodstream could be its access into the abdominal cavity through tubal reflux, thus resulting in absorption by peritoneal lymphatic vessels. Despite the mechanisms proposed, doubts still persist about the real mechanism of CA125 release into the circulation, considering that retrograde menstruation is still controversial and that the levels of this marker change during the postmenopausal period.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The CA125 released by the endometrium may reach the blood stream and lymphatic circulation via the peritoneal route, starting from retrograde menstruation, thereby allowing contact with local inflammatory reactions and thus releasing coelomic CA125. 20 Another explanation for the increased levels of CA125 in the bloodstream could be its access into the abdominal cavity through tubal reflux, thus resulting in absorption by peritoneal lymphatic vessels. Despite the mechanisms proposed, doubts still persist about the real mechanism of CA125 release into the circulation, considering that retrograde menstruation is still controversial and that the levels of this marker change during the postmenopausal period.…”
Section: Discussionmentioning
confidence: 99%
“…However, a functional rather than quantitative change of the endometrium still may be at the origin of CA-125 changes (7). Observations reported in the literature agree that CA-125 levels rise during the menstrual period as a consequence of endometrial disruption (18,19). This is probably due to an easier access of CA-125 from the endometrial epithelial lining into the circulation during menstruation (20).…”
Section: Discussionmentioning
confidence: 79%
“…Some hypotheses tried to explain this increase: presence of blood and eutopic endometrial tissue into the peritoneal cavity due to retrograde menses, enlarged surface of endometrial tissue, and inflammatory reaction in the endometrial foci [18]. Bon et al suggested that CA-125 released from the endometrium can have access to the lymphatics and the circulation [19].…”
Section: Discussionmentioning
confidence: 99%